The Value of Liquid Biopsies for Guiding Therapy Decisions in Non-small Cell Lung Cancer - Saarenheimo, Jatta; Eigeliene, Natalja; Andersen, Heidi; Tiirola, Marja; Jekunen, Antti (Frontiers in Oncology, 2019)
Targeted therapies have allowed for an individualized treatment approach in non-small-cell lung cancer (NSCLC). The initial therapeutic decisions and success of targeted therapy depend on genetic identification of personal tumor profiles. Tissue biopsy is the gold standard for molecular analysis, but non-invasive or minimally invasive liquid biopsy methods are also now used in clinical practice, allowing for later monitoring and optimization of the cancer treatment. The inclusion of liquid biopsy in the management of NSCLC provides strong evidence on early treatment response, which becomes a basis for determining disease progression and the need for changes in treatment. Liquid biopsies can drive the decision making for treatment strategies to achieve better patient outcomes. Cell-free DNA and circulating tumor cells obtained from the blood are promising markers for determining patient status. They may improve cancer treatments, allow for better treatment control, enable early interventions, and change decision making from reactive actions toward more predictive early interventions. This review aimed to present current knowledge on and the usefulness of liquid biopsy studies in NSCLC from the perspective of how it has allowed individualized treatments according to gene profiling and how the method may alter the treatment decisions in the future.